THE ROLE OF MUSIC IN RAISING CHILDREN - Gulayim Tilepova; Ayapova Khurliman (International Engineering Journal For Research & Development, 2022)
To study the role of music and music lessons as one of the most effective tools for developing the abilities of preschool children and to substantiate them on the basis of various comparative analytical studies.